2011
DOI: 10.1159/000332835
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Physiological and Anti-Inflammatory Effect of Montelukast in Patients with Cough Variant Asthma

Abstract: Background: Cough variant asthma (CVA) is a phenotype of asthma presenting solely with coughing, characterized by airway hyperresponsiveness, eosinophilic inflammation and a cough response to bronchodilators. Leukotriene receptor antagonists (LTRAs) are antiasthma medications with anti-inflammatory and bronchodilatory properties. Although LTRAs exert antitussive effects in CVA, the mechanisms involved are unknown. Objectives: This study aimed to clarify the antitussive mechanisms of LTRAs in CVA patients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 111 publications
4
49
0
6
Order By: Relevance
“…In a small, randomized, double-blind, placebocontrolled trial, a 4-week course of montelukast significantly improved subjectively rated cough frequency, with beneficial effects noted by the second week of therapy (Spector and Tan, 2004). In a prospective, observational study of 23 adult nonsmokers with CVA, a 4-week course of montelukast significantly improved subjective cough scores, and diminished cough reflex sensitivity to capsaicin, as well as sputum eosinophil counts, whereas not affecting pulmonary function, airway responsiveness to methacholine, or sputum mediator levels (Takemura et al, 2012). Another study of adults with CVA demonstrated the efficacy of a 2-week course of montelukast against subjectively rated cough, but the agent was ineffective against cough in atopic subjects (Kita et al, 2010).…”
Section: J Leukotriene Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small, randomized, double-blind, placebocontrolled trial, a 4-week course of montelukast significantly improved subjectively rated cough frequency, with beneficial effects noted by the second week of therapy (Spector and Tan, 2004). In a prospective, observational study of 23 adult nonsmokers with CVA, a 4-week course of montelukast significantly improved subjective cough scores, and diminished cough reflex sensitivity to capsaicin, as well as sputum eosinophil counts, whereas not affecting pulmonary function, airway responsiveness to methacholine, or sputum mediator levels (Takemura et al, 2012). Another study of adults with CVA demonstrated the efficacy of a 2-week course of montelukast against subjectively rated cough, but the agent was ineffective against cough in atopic subjects (Kita et al, 2010).…”
Section: J Leukotriene Receptor Antagonistsmentioning
confidence: 99%
“…Although there is some evidence that LTRAs can have modest anti-inflammatory effects and that their ability to improve subjective and objective parameters in asthmatic patients is well established, the mechanism by which these agents may function as antitussives remains poorly understood. A reasonable assumption is that the LTRAs inhibit cough in asthmatics through their inhibition of eosinophilic airway inflammation (Takemura et al, 2012). However, a recent study in severe asthmatics demonstrating that anti-IL-5 therapy had significant beneficial effect on the frequency of severe exacerbations without an effect on cough calls into question a causal relationship between eosinophilic inflammation and cough in patients with asthma (Haldar et al, 2009).…”
Section: J Leukotriene Receptor Antagonistsmentioning
confidence: 99%
“…However, patients with CVA in the real world cannot inhale deeply and severe coughing interrupts breathing; thus oral LTRAs might be reasonable add-ons or alternatives for such patients. Montelukast has significantly reduced cough symptoms and suppressed airway inflammation [48]. One study compared the antitussive effects of pranlukast and LABA in patients with CVA and found that pranlukast can significantly reduce cough scores [49].…”
Section: Cough Variant Asthma (Cva)mentioning
confidence: 99%
“…Asthma is a chronic inflammatory disorder of the airways 1 . It is a heterogeneous disease, with different underlying disease processes.…”
Section: Introductionmentioning
confidence: 99%